Insecticidal activity of a Melinis minutiflora grass extract on Stomoxys calcitrans flies (2011)
ABSTRACT: Several extraction methods were utilized to study the insecticidal activity of a Melinis minutiflora grass extract. Four concentrations (10, 20, 40, 80%) of the product which had the highest yield (i.e., a wax-free hexane extract) were tested to establish its insecticidal activity on S. calcitrans flies (adults and larvae). It is hypothesized that an 80% plant extract has a lethal effect similar to or higher than cypermethrin on flies and larvae. Mortality rates were assessed by survival analysis comparing the Kaplan-Meier mortality curves against the standard pyrethroid (cypermethrin) or against the solvent (ethyl acetate). The median mortality (time to kill 50% of the population) of adult flies exposed to cypermethrin over an eight-hour period was one hour, while it was three hours for the highest concentration of the extract tested. Both medians were significantly lower than those of the other treatments. The median mortality of larvae exposed to cypermethrin for a 30 minute period was four minutes, while it was eight minutes for the highest concentration (80%) of the plant extract. These values were significantly lower than the medians obtained for the other concentrations of the extract. These data suggest that extracts obtained from Melinis minutiflora grass could be a safe substitute for chemical insecticides.